Revised Token Test in Kannada - NR, Veena (Journal of All India Institute of Speech and Hearing)
Aphasia is a many faceted problem as the complexity of the problem accounts for the diversity of approaches among investigators from various specialities. It has been defined differently and classified differently. But most of them agree upon the facts that aphasia is a language disorder due to brain damage. Like- wise there are many tests to test aphasia. But objections have always been made to these tests. It has been frequently reported that aphasic responses are inconsistent and so test results are not reliable. Criticisms have been levelled against plus-minus scoring system and quantification of data. Some clinicians consider that the test procedures are traumatic to patients. The most frequent complaint is that comprehensive testing is economically unfeasible because it requires too much time.